CHALLENGES OF A GLOBAL PMIS IMPLEMENTATION - A perspective of regional headquarters - Hakmeh, Sofie (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Project management information systems (PMIS) is emerging as an essential tool to support project managers and project stakeholders in multi-project environments. PMIS automates the full lifecycle of a project acts as a centralized source to input and retrieve project information. Much of the current research on PMIS focuses only on the benefits and the impact of the tool on the organization, this research is a case study of the challenges of the global rollout of a PMIS tool from the perspective of a regional headquarters. Ten research propositions are formulated from existing literature surrounding challenges of PMIS implementation and challenges of global information system implementations. These research propositions are then investigated through semi-structured interviews with employees of the regional headquarters of a multinational organization that is globally implementing a PMIS tool. The results supported the validity of three research propositions originating from the challenges of PMIS implementation and six research propositions originating from the challenges of the global implementation of information systems. Three additional challenges were noted as emerging themes. This research expands the body of literature on PMIS implementations and highlights the challenges specifically for a global implementation of this tool.